Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22094522
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Genetic Resources for Cobalamin (Vitamin B12) Biosynthesis: From Ecosystems to Industrial Biotechnology

Abstract: Many microbial producers of coenzyme B12 family cofactors together with their metabolically interdependent pathways are comprehensively studied and successfully used both in natural ecosystems dominated by auxotrophs, including bacteria and mammals, and in the safe industrial production of vitamin B12. Metabolic reconstruction for genomic and metagenomic data and functional genomics continue to mine the microbial and genetic resources for biosynthesis of the vital vitamin B12. Availability of metabolic enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 113 publications
(475 reference statements)
1
36
0
1
Order By: Relevance
“…According to Lu et al [41], only about 10% of 155 soil microbial metagenomes contained complete cobalamin biosynthetic pathway. Similar results were obtained by Balabanova et al [42], who found that the primary producers of cobalamin in the soil microbiome were bacteria of the genera Proteobacteria, Actinobacteria, Firmicutes, and Nitrospirae, which made up a small percentage of the community. The remaining microorganisms were only able to transport cobalamin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to Lu et al [41], only about 10% of 155 soil microbial metagenomes contained complete cobalamin biosynthetic pathway. Similar results were obtained by Balabanova et al [42], who found that the primary producers of cobalamin in the soil microbiome were bacteria of the genera Proteobacteria, Actinobacteria, Firmicutes, and Nitrospirae, which made up a small percentage of the community. The remaining microorganisms were only able to transport cobalamin.…”
Section: Discussionsupporting
confidence: 89%
“…One explanation for this phenomenon is that there are still undiscovered pathways in the biosynthesis of tetrapyrrole cofactors in bacteria [43]. However, incomplete pathways, including pathways in which microorganisms uptake readymade tetrapyrrole cofactors such as heme [44][45][46] and cobalamin [2,41,42] from the environment, have also been established. These studies have emphasized that the microorganisms transport cofactors from external sources.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the evolution of the cyanocobalamin synthesis pathway allowed the fermentation of small molecules such as ethanolamine, 1,2-propanediol, and glycerol in anaerobic environments [ 20 ]. De novo cobalamin synthesis occurs in bacteria and archaea, and some species also may synthesize cobalamin by absorbing corrinoids through the salvage pathway [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, the phosphoribosyltransferase CobU/T (EC 2.4.2.21) introduces the DMBI via a nucleophilic substitution reaction [ 34 ]. This pathway was firstly described for S. meliloti [ 35 ] and later found in the majority of Cbl-producing bacteria [ 36 ], including the two most important industrial producers, P. freudenreichii [ 37 ] and P. denitrificans [ 38 ]. This fact highlighted the incapacity of P. freudenreichii to completely produce Cbl anaerobically without any external addition of DMBI.…”
Section: Biosynthesis Of Vitamin B 12 : the Aerobi...mentioning
confidence: 99%